2022
DOI: 10.3390/su14159529
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological Effects of Pesticides on Hematological Parameters and Oxidative Enzymes in Freshwater Catfish, Mystus keletius

Abstract: Hematological parameters and changes in stress-induced functionalities of cellular enzymes have been recognized as valuable tools for monitoring fish health and determining the toxic effects of pesticides. The present study was conducted to evaluate the toxic effect of selected pesticides viz., Ekalux (EC-25%), Impala (EC-55%), and Neemstar (EC-15%) on freshwater catfish Mystus keletius. Fish were exposed to sub-lethal concentrations (mg/L) of the selected pesticide for a period of 7, 14, 21, and 28 days. Hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Blood parameters are used as physiological indicators in response to external or internal changes in fish. Several studies in aquatic animals revealed that exposure to nano and microplastics caused disorders in the immune system (Barathinivas et al, 2022; Li et al, 2020; Saha, Dhara, Pal, et al, 2023; Saha, Dhara, Chukwuka, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Blood parameters are used as physiological indicators in response to external or internal changes in fish. Several studies in aquatic animals revealed that exposure to nano and microplastics caused disorders in the immune system (Barathinivas et al, 2022; Li et al, 2020; Saha, Dhara, Pal, et al, 2023; Saha, Dhara, Chukwuka, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of marine organisms to pollutants results in molecular alterations and in structural and functional changes that can be detrimental for animal fitness [40,58,59]. The evaluation of these events takes advantage of the analysis of well-established biological markers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the common carp ( Cyprinus carpio ), stands as a highly adaptable and widely cultivated freshwater fish species. Its utilization in studies is particularly valuable in the context of evaluating the overall health of aquatic ecosystems [ [45] , [46] , [47] , [48] ]. In the context of pesticide pollution, C. carpio specimens' exposure to these contaminants is mainly attributed to the widespread cultivation of this fish in earthen ponds located near agricultural fields [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%